Hematinic deficiencies and anemia statuses in oral mucosal disease patients with folic acid deficiency - Julia Yu-Fong Chang; Yi-Ping Wang; Yang-Che Wu; Shih-Jung Cheng; Hsin-Ming Chen; Andy Sun (Journal of the Formosan Medical Association, 2015)
Folic acid deficiency (FAD) may result in macrocytic anemia. This study assessed the hematinic deficiencies and anemia statuses in oral mucosal disease patients with FAD (defined as folic acid ≤ 6 ng/mL). Methods: The blood hemoglobin (Hb), iron, vitamin B12, and folic acid concentrations, serum gastric parietal cell antibody level, and mean corpuscular volume (MCV) in 198 oral mucosal disease patients with FAD were measured. Based on World Health Organization (WHO) criteria, anemia or Hb deficiency was defined as having an Hb concentration of <13 g/dL for men and <12 g/dL for women. In this study, macrocytic anemia due to FAD was defined as having an MCV ≥100 fL and folic acid ≤6 ng/mL; pernicious anemia as having MCV ≥100 fL, vitamin B12 < 200 pg/mL, and serum gastric parietal cell antibody positivity; iron deficiency anemia as having MCV <80 fL and iron <60 μg/dL; and thalassemia trait as having MCV <74 fL, red blood cell (RBC) count > 5.0 × 1012/L, and Mentzer index (MCV/RBC) < 13. Results: We found that by WHO definitions, 73 (36.9%), 41 (20.7%), and 10 (5.1%) of our 198 FAD patients had concomitant Hb, iron, and vitamin B12 deficiencies, respectively. Of 73 anemic FAD patients, three had macrocytic anemia due to FAD, one had pernicious anemia, 14 had iron deficiency anemia, eight had thalassemia trait, and the resting 47 had normocytic anemia. Conclusion: In addition to macrocytic anemia (2.0%), FAD patients may have concomitant normocytic (23.7%) or microcytic (11.1%) anemia.